Remote Terminal Unit (RTU) Hardware Design And Development For Distribution Automation System - Ab Ghani, Mohd Ruddin; Wan Jusoh, Wan Nor Shela Ezwane; Mat Hanafiah, Mohd Ariff; Raman, Siti Hajar (2014)
This paper introduces the design and development of Remote Terminal Unit (RTU) circuit and hardware implementation which represented in Distribution Automation System (DAS. The design is based on microcontroller using PIC16F877A and also introduces the Orcad software to design circuit for the RTU. RTU is a standalone data used to monitor status and alarm, sequence of events, counters/pulse accumulators, binary code decimals and analog inputs. The function of RTU is to collects all the data from the plant, digitize them and send to the master station through the communication network. RTU also receives command from control center (master station) and executes it at the substation.